Socialization and Workshop of Coding Based on ICD-10 and ICD-9 Cm Regulations at Mental Hospital Prof Hb Saanin Padang - Sayati Mandia; Nurhasanah Nasution (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Coding based on ICD-10 is assigning codes using letters and numbers representing data components to ensure code accuracy. In coding patient medical actions/procedures, coders use ICD-9 CM rules to assign medical action codes to the patient's resume sheet. The application of coding is used to index disease records, input for medical diagnosis reporting systems, facilitate the process of storing and retrieving data related to diagnosis, characteristics of patients and service providers, basic ingredients in grouping DRGs (diagnostic-related groups) for service fee payment billing systems, national and international reporting morbidity and mortality, tabulation of health service data for the evaluation process of medical service planning, analysis of health service financing, as well as for epidemiological and clinical research. Mental Hospital, Prof HB Saanin Padang is a mental hospital under the government of West Sumatra. To improve the quality of medical recorders and avoid losses in insurance financing claims, the service will carry out Community Service (PKM) activities. This service aims to provide socialization and training on coding diagnoses and actions based on ICD-10 and ICD-9 CM regulations. The PKM activity is a development program where the service team carries out outreach regarding regulations for coding diagnoses and actions based on ICD-10 and ICD-9 CM. Then the team will carry out follow-up activities in the form of ICD-10 and ICD-9 CM coding practices with partners. The partner in this community service activity is the Prof HB Saanin Padang Mental Hospital (RSJ). Based on the topics, several activities consist of socialization of regulations ICD 10 and ICD-9 CM and workshop study case based on ICD 10 and ICD-9 CM regulations. This activity has been done on Mei 07, 2024. Results showed there is increasing knowledge about regulation ICD 10 and ICD-9 CM based on pre-test and post-test results.